Leiomyisarcoma of the duodenum - El Ters, Escandor; Piazze, Alvaro; Miranda, Elber; Bañales, Cecilia; González, Fernando; Terra, Daniel; Pérez Penco, Ernesto; Estrugo, Roberto (Cirugía del Uruguay, 1997)
The authors present a case of leiomyosarcoma of the duodenum of difficult diagnosis, treated by means of local resection and reoperated because of tumoral recidive, who is undergoing adjuvant treatment with chemotherapy and radiation therapy. They analyse national and international literature and point out its higher frequency in the fifth decade; the following are predominant symptoms: abdominal .pain, digestive bleeding and tumor, more frequent in the second and third portian of the duodenum; elective surgical treatment is proposed and global 5 year survival rafe is of 50%.